2021
DOI: 10.3389/fphar.2020.588309
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Point-of-Care A1C Tests in a Primary Care Setting

Abstract: Objective: We evaluated the cost-effectiveness of the point-of-care A1c (POC-A1c) test device vs. the traditional laboratory dosage in a primary care setting for people living with type 2 diabetes.Materials and Methods: The Markov model with a 10-year time horizon was based on data from the HealthRise project, in which a group of interventions was implemented to improve diabetes and hypertension control in the primary care network of the urban area of a Brazilian municipality. A POC-A1c device was provided to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Opportunities were identified in services that use multiple care technologies towards providing comprehensive care for NCD. Innovative technologies used in local PHC, like the fingertip glycated hemoglobin tester and home blood pressure monitoring, were identified as facilitators for improving access to glycemic and pressure control, both in screening and therapeutic follow-up actions [34,35]. The reception and bonding are also recognized as a technology of relationships and advocated in Brazil, as a care practice based on the lasting and authentic relationship, mutual understanding, and sense of affiliation [36], stimulating lifestyle changes, and increasing responsibilities and adherence to treatment [22,31], however more difficult to operationalize due to the great demand for individual care.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunities were identified in services that use multiple care technologies towards providing comprehensive care for NCD. Innovative technologies used in local PHC, like the fingertip glycated hemoglobin tester and home blood pressure monitoring, were identified as facilitators for improving access to glycemic and pressure control, both in screening and therapeutic follow-up actions [34,35]. The reception and bonding are also recognized as a technology of relationships and advocated in Brazil, as a care practice based on the lasting and authentic relationship, mutual understanding, and sense of affiliation [36], stimulating lifestyle changes, and increasing responsibilities and adherence to treatment [22,31], however more difficult to operationalize due to the great demand for individual care.…”
Section: Discussionmentioning
confidence: 99%
“…These complications, in addition to significantly affecting the quality of life and survival of people with diabetes, have a high financial impact on health systems. In Brazil, the available data have attributed an average annual cost with complications related to diabetes between 112.90 and 3917.00 dollars per patient/patient/year, which depends on the type of complication presented, resulting from inadequate control ( 17 ). When considering these values, the estimated cost for the local health system with complications related to diabetes ranges from 17,047.90 to 591,467.00 dollars, only for patients from these four locations whose HbA1c levels were higher than the control threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The initiative made it possible to measure HbA1c in people who needed it in these areas. In addition, we recently demonstrated that this type of technology can be cost-effective if applied in primary care units in urban areas ( 17 ). Given the findings obtained with the application of point-of-care for HbA1c measurement in rural communities, we believe that the cost-effectiveness ratio of the initiative is even more favorable when compared to testing in laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For diabetic patients, HbA1c levels were measured using the portable Abbott Afinion ™ two Analyzer, a point-of-care device that allows for instant evaluation without needing to visit a clinical laboratory. In a study, "the Cost-Effectiveness study of Point-of-Care A1C Tests in a Primary Care Setting," because the point-of-care testing of HbA1c levels resulted in an increase in the rate of diabetes control, the higher purchase costs of the point-ofcare testing compared to that of laboratory tests, were reportedly offset by the savings from the reduction in diabetes-related complications and hospitalizations (Rosa et al, 2021). BP and HbA1c levels were measured again within 3 months of the intervention, for each patient.…”
Section: Methodsmentioning
confidence: 99%